Fatty liver index and development of lung cancer: a nationwide cohort study - Jihye Lim; Bongseong Kim; Kyungdo Han; Jeong Uk Lim (The Korean Journal of Internal Medicine)
Background/Aims This study aimed to evaluate the impact of steatotic liver disease severity on the cumulative incidence of lung cancer utilizing data from the Korea National Health Insurance Service (NHIS). Methods This study examined the risk of lung cancer in the general population in conjunction with the incidence of steatotic liver disease. The study population consisted of 3,261,438 individuals aged 20 years or older who underwent a general health examination in 2009. Results Individuals with fatty liver index (FLI) of 30–59 exhibited a 1.08-fold increased risk of lung cancer (95% CI: 1.04–1.11), while FLI ≥ 60 was associated with a 1.22-fold elevated risk of lung cancer (95% CI: 1.17–1.28) compared to those with FLI < 30. The risk varied with smoking status; in current smokers, the adjusted HR for the FLI 30–59 group was 1.05 (95% CI: 1.00–1.10), while that in the FLI ≥ 60 group was 1.11 (95% CI: 1.04–1.18). In never- or past-smokers, the adjusted HR for the FLI 30–59 group was 1.10, and that for the FLI ≥ 60 group was 1.31. Subgroup analysis revealed an incidence rate of 1.06 per 1,000 person-years in the consistently high FLI group compared to 1.15 in those with improved FLI. Improving FLI over time was associated with a 0.93-fold decrease in lung cancer risk. Conclusions Our study demonstrated a correlational relationship between lung cancer incidence and the severity of steatotic liver disease as measured by FLI.